Careers in graphic arts and computer graphics - McGuire-Lytle, Erin frey50 (New York : Rosen Pub. Group, 1999)
Provides information on job opportunities in the field of graphic arts, discussing educational requirements, specific types of jobs, and the impact of computers on the way graphic artists work.
Includes bibliographical references (p. 125-127) and index.
76571
Keywords: Graphic arts -- Juvenile literature. -- Vocational guidance; Graphic arts -- Vocational guidance; Vocational guidance